Loss of CPEB3 Upregulates MEGF10 to Impair Mosaic Development of ON Starburst Amacrine Cells - Chen, Yin-Peng; Bai, Geng-Shuo; Wu, Meng-Fang; Chiao, Chuan-Chin; Huang, Yi-Shuian (Frontiers in Molecular Neuroscience, 2016)
Cytoplasmic polyadenylation element binding protein 3 (CPEB3) regulates target RNA translation in neurons. Here, we examined CPEB3 distribution and function in the mouse retina. CPEB3 is expressed in retinal neurons, including those located in the inner nuclear layer (INL) and ganglion cell layer (GCL) but not in cone and rod photoreceptors in the outer nuclear layer. A previous study found CPEB3 expressed in cholinergic starburst amacrine cells (SACs). We first examined these cells and observed aberrant SAC mosaicism in CPEB3-knockout retinas. Retinal neurons showed orderly spatial arrangements. Many individual subtypes are organized non-randomly in patterns called mosaics. Despite CPEB3 being expressed in both populations of SACs, OFF SACs in the INL and ON SACs in the GCL, aberrant mosaic regularity was observed in only ON SACs of CPEB3-knockout retinas. Molecular characterization revealed that translation of multiple epidermal growth factor 10 (Megf10) RNA is suppressed by CPEB3 during the first week of postnatal development, when MEGF10 is primarily expressed in SACs and mediates homotypic repulsive interactions to define intercellular spacing of SACs. Thus, elevated MEGF10 expression in the absence of the translational repressor CPEB3 may account for defective spatial organization of ON SACs. Our findings uncover for the first time that translational control plays a role in shaping retinal mosaic arrangement.